Isaiah in the New Testament - Moyise, Steve; Menken, M. J. J. (New Testament and the Scriptures of Israel., 2005)
Isaiah in the New Testament brings together a set of specially commissioned studies by authors who are experts in the field. After an introductory chapter on the use of Isaiah in the Dead Sea Scrolls and second temple literature, each of the New Testament books that contain quotations from Isaiah are discussed: Matthew, Mark, Q, Luke-Acts, John, Romans & Galatians, 1 & 2 Corinthians, Hebrews, 1 Peter, Revelation. The book provides an overview of the status, role and function of Isaiah in the first century. It considers the Greek and Hebrew manuscript traditions and offers insights into the var.